(untitled) (Research, Society and Development, 2020)
The teaching of mathematics to students with intellectual disabilities, through computerized procedures or not, has been the subject of investigation, for more than two decades, by Behavior Analysis. Recently, the use of educational games, analog or digital, have also become objects of studies for teaching different skills. Thus, this article aimed to present the mapping of Brazilian studies on digital games, which adopted the assumptions of Behavior Analysis in its elaboration and were specifically directed to the teaching of mathematical skills to students with intellectual disabilities. Studies between 2009 and 2020 were selected using the terms: behavior analysis, digital games, elementary school, mathematics and intellectual disability. The consultation took place in two databases (Google Scholar and Capes’ Theses and Dissertations Catalog), based on the Systematic Literature Review Protocol (RSL). The absence of studies that covered all terms, redirected the systematization and analysis of the data, considering the specific relationships between the terms. Thirteen studies were selected and analyzed, with only four using digital games for teaching mathematics. The participation of students with intellectual disabilities was found only in studies that used non-computerized procedures, computerized and analog educational games, with satisfactory results. The mapping indicated the need for studies that articulate these experiences, which could contribute to the advancement of the area and the school inclusion of students with intellectual disabilities.